FUTURE ENGINEERS PROFESSIONAL COMPETENCE DEVELOPMENT MODEL THROUGH DIGITAL TECHNOLOGIES (Global Conference on Medical and Health Sciences, 2026)
In the article modern education in the system engineering in the field bachelor's degree students for professional competence formation and in development digital of technologies role open This is also given. competence to form service doer model structure, composition parts, practical mechanisms and pedagogical conditions scientific basically illuminated.
Keywords: Engineering education, digital technologies, professional competence, innovative model, information and communication technologies (ICT), digital pedagogy.